Phase change material and memory
By doping the matrix material with Hf and A elements in the phase change memory, the operating speed and durability of the phase change memory are improved, solving the technical problem of balancing speed and durability, and achieving more efficient storage performance.
Patent Information
- Application Number
- CN202411243290.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
AI Technical Summary
How to balance the operating speed and durability of phase-change memory in order to overcome the limitation of the von Neumann bottleneck on the improvement of computer system performance.
By doping the phase change material with Hf and A elements, where A includes at least one of N, O and Si, the composition of the matrix material is optimized to improve the crystallization temperature and thermal stability, and to enhance the adhesion between the phase change material and the electrode.
It improves the write speed and cycle endurance of phase-change memory, enhances the resistance window and performance reliability, and is suitable for mass production.
Smart Images

Figure CN119300702A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of storage technology, and in particular to a phase change material and a memory. Background Art
[0002] In response to the limitation of von Neumann bottleneck on the performance improvement of computer systems, the industry has proposed a storage-class memory (SCM) with a storage speed and capacity between dynamic random access memory (DRAM) and flash memory. Among them, phase change memory is one of the few storage-class memory options that has been mass-produced first. According to its application positioning, the performance requirements for phase change memory are both operating speed and durability.
[0003] Therefore, how to strike a balance between the operating speed and durability of phase change memory is a technical problem that needs to be solved. Summary of the invention
[0004] The present application provides a phase change material and a memory to balance the operating speed and durability of the memory.
[0005] In a first aspect, the present application provides a phase change material, the phase change material comprising:
[0006] Base material;
[0007] The Hf element; and
[0008] The A element includes at least one element selected from the group consisting of N, O and Si.
[0009] In some embodiments, in the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%.
[0010] In some embodiments, in the phase change material, the atomic number percentage of the A element is greater than 0% and less than or equal to 20%.
[0011] In some embodiments, the A element includes at least one of N and O.
[0012] In some embodiments, in the phase change material, an absolute value of a difference between an atomic percentage of the Hf element and an atomic percentage of the A element is less than or equal to 1%.
[0013] In some embodiments, the matrix material includes at least one element of Ge, Sb, and Te.
[0014] In some embodiments, the matrix material includes Ge, Sb and Te;
[0015] In the phase change material, the atomic number percentage of Ge element is greater than or equal to 0% and less than or equal to 50%, the atomic number percentage of Sb element is greater than or equal to 10% and less than or equal to 50%, and the atomic number percentage of Te element is greater than or equal to 40% and less than or equal to 70%.
[0016] In some embodiments, the phase change material has the general chemical formula (N) x1 (Hf) y1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1 ; Among them, x1 represents the atomic number percentage of N element, y1 represents the atomic number percentage of Hf element, m1 / n1 / k1 represents the atomic number percentage of Ge, Sb and Te, 0<x1≤10%, 0<y1≤10%, 0≤m1≤50%, 0≤n1≤50%, 40%≤k1≤70%.
[0017] In some embodiments, the phase change material includes (Ge 10 Sb 40 Te 50 ) 91 Hf5N4、(Ge 12.5 Sb 37.5 Te 50 ) 91 Hf5N4、(Ge1 2.5 Sb 37.5 Te 50 ) 88 Hf8N4 and (Ge 11.12 Sb 44.44 Te 44.44 ) 91 At least one of Hf5N4.
[0018] In some embodiments, the crystallization temperature of the phase change material is greater than or equal to 150°C and less than or equal to 300°C.
[0019] In some embodiments, the resistance window of the phase change material is greater than or equal to 1 and less than or equal to 20,000.
[0020] In a second aspect, the present application further provides a memory chip, the memory chip comprising a memory unit, the memory unit comprising a phase change layer and two electrodes respectively arranged on both sides of the phase change layer, the phase change layer comprising the phase change material of any of the above embodiments.
[0021] In some embodiments, the adhesion between the electrode and the phase change layer is characterized by an energy release rate, and the energy release rate is greater than or equal to 0.8 J / m2 .
[0022] In a third aspect, the present application further provides a memory, comprising a memory chip according to any of the above embodiments and a controller, wherein the controller is connected to the memory chip, and the controller is used to control the memory chip.
[0023] In some embodiments, the writing speed of the memory is greater than or equal to 50ns / time.
[0024] In some embodiments, the memory has a cycle capacity greater than or equal to 10 8 Second-rate.
[0025] In the phase change material, memory chip and memory provided in some embodiments of the present application, Hf element and A element are doped simultaneously in the matrix material, and A element includes at least one element of N, O and Si. In this way, Hf element and A element are doped simultaneously in the matrix material, which can increase the crystallization temperature of the phase change material, thereby increasing the thermal stability of the phase change material in the amorphous state, and can also increase the write (SET) speed of the memory including the phase change material, thereby increasing the operation speed of the phase change memory. In addition, Hf element and A element are doped simultaneously in the matrix material, which can also increase the cycle endurance and resistance window of cycling between the write process and the erase (Reset) process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A block diagram of a memory according to some embodiments of the present application;
[0027] Figure 2 A schematic diagram of the structure of a memory chip in some embodiments provided in this application;
[0028] Figure 3 A schematic diagram of the structure of a memory chip according to some other embodiments of the present application;
[0029] Figure 4 A schematic diagram of the structure of a memory chip according to some other embodiments of the present application;
[0030] Figure 5 The resistance-temperature curve test result diagram of the phase change material of Example 1, wherein d11 is a heating curve and d12 is a cooling curve;
[0031] Figure 6 4 is a test result diagram of the cycle characteristics of Example 4, where RST corresponds to the erase cycle curve and SET corresponds to the write cycle curve;
[0032] Figure 750ns is a curve corresponding to a write speed of 50ns, 100ns is a curve corresponding to a write speed of 100ns, and 150ns is a curve corresponding to a write speed of 150ns;
[0033] Figure 8 1 is a test result diagram of the resistance window of Example 4, where Rrst is the resistance corresponding to the erase operation, and Rset is the resistance corresponding to the write operation.
[0034] The reference numerals are as follows:
[0035] 300, memory; 100, storage chip; 200, controller;
[0036] 10. Storage unit;
[0037] 11, first memory cell; 111, first bottom electrode; 112, first selection layer; 113, first middle electrode; 114, first phase change layer; 115, first top electrode;
[0038] 12, second storage unit; 121, second bottom electrode; 122, second selection layer; 123, second middle electrode; 124, second phase change layer; 125, second top electrode;
[0039] 131, first bit line; 132, second bit line;
[0040] 141, first word line; 142, second word line;
[0041] z, first direction; x, second direction; y, third direction;
[0042] 21, substrate layer; 22, dielectric layer; 221, sink hole; 23, first electrode; 231, columnar contact portion; 232, lead portion; 24, second electrode; 25, phase change layer. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0044] Phase-Change Memory (PCM) is a memory technology that uses phase-change materials as storage media. The Joule heat generated by electrical pulses or light pulses is used to cause the phase-change material to undergo a reversible phase change between the amorphous state (the phase-change material is in a high-resistance state) and the crystalline state (the phase-change material is in a low-resistance state) to achieve data writing and erasing, and reading is achieved by measuring the size of the resistance.
[0045] Figure 1 The block diagram of the memory of some embodiments provided in the present application. The memory 300 includes a memory chip 100 and a controller 200, and the memory chip 100 is connected to the controller 200. The controller 200 is used to control the memory chip 100 to implement data writing, erasing and reading.
[0046] Figure 2 This is a schematic diagram of the structure of the memory chip of some embodiments provided in this application. Figure 2 As shown, the memory chip 100 may adopt a cross-lattice structure. For the memory chip 100 adopting the cross-lattice structure, the bit density of the memory chip 100 can be improved by stacking a plurality of memory cells 10. Furthermore, the two ends of the memory cell 10 are connected and led out through mutually crossed electrode wires.
[0047] like Figure 2 As shown, the memory chip 100 includes a first memory cell 11 and a second memory cell 12 stacked along a first direction z. The first memory cell 11 includes a first bottom electrode 111, a first gating layer 112, a first intermediate electrode 113, a first phase change layer 114, and a first top electrode 115 stacked in sequence. The second memory cell 12 includes a second bottom electrode 121, a second gating layer 122, a second intermediate electrode 123, a second phase change layer 124, and a second top electrode 125 stacked in sequence. The second top electrode 125 is disposed close to the first bottom electrode 111.
[0048] The memory chip 100 further includes a first word line 141, a second word line 142, a first bit line 131, and a second bit line 132. In the first direction z, the first word line 141 and the second word line 142 are located between the first memory cell 11 and the second memory cell 12. The first word line 141 is connected to the first bottom electrode 111 of the first memory cell 11, the first bit line 131 is located at a side of the first memory cell 11 away from the first word line 141 and is connected to the first top electrode 115 of the first memory cell 11. The second word line 142 is connected to the second top electrode 125 of the second memory cell 12, the second bit line 132 is located at a side of the second memory cell 12 away from the second word line 142 and is connected to the second bottom electrode 121 of the second memory cell 12. The first word line 141 and the second word line 142 extend along the second direction x. The first bit line 131 and the second bit line 132 extend along the third direction y. The first direction z, the second direction x, and the third direction y intersect with each other.
[0049] The first bottom electrode 111, the first intermediate electrode 113, the first top electrode 115, the second bottom electrode 121, the second intermediate electrode 123 and the second top electrode 125 may include at least one of amorphous carbon (aC), carbon nanotubes, graphene and tungsten and other conductive materials. In a specific embodiment, the first bottom electrode 111, the first intermediate electrode 113, the first top electrode 115, the second bottom electrode 121, the second intermediate electrode 123 and the second top electrode 125 may include amorphous carbon.
[0050] The first gate layer 112 and the second gate layer 122 may include a chalcogenide material, such as Zn x Te y ,Ge x Te y , Nb x O y or Si x As y Te z wait.
[0051] The first word line 141 , the second word line 142 , the first bit line 131 and the second bit line 132 include a conductive material, including but not limited to tungsten (W), cobalt (Co), copper (Cu), aluminum (Al), polysilicon, doped silicon, silicide, or any combination thereof.
[0052] Figure 3 Schematic diagram of the structure of the memory chip of some other embodiments provided by the present application. Figure 3 As shown, the memory chip 100 adopts a small-size electrode contact structure, and the electrode on at least one side of the phase change layer adopts a small-size contact structure (eg, a columnar contact structure) to achieve the size definition of the memory cell 10 .
[0053] like Figure 3 As shown, the memory chip 100 includes a substrate layer 21, a dielectric layer 22, a first electrode 23, a second electrode 24 and a phase change layer 25. The first electrode 23, the second electrode 24 and the phase change layer 25 constitute a memory cell 10. The dielectric layer 22 is disposed on the substrate layer 21. The first electrode 23 is buried in the dielectric layer 22. The first electrode 23 includes a columnar contact portion 231 and an extraction portion 232, and the columnar contact portion 231 and the extraction portion 232 are bent relative to each other and connected. The phase change layer 25 is in a layered shape. The phase change layer 25 is disposed on a side of the dielectric layer 22 away from the substrate layer 21 and is in contact with the columnar contact portion 231, and the portion where the columnar contact portion 231 contacts the phase change layer 25 defines a phase change region. The second electrode 24 is in a layered shape. The second electrode 24 is disposed on a surface of the phase change layer 25 away from the substrate layer 21. By applying a voltage V to the second electrode 24 and the extraction portion 232 of the first electrode 23, the phase change layer 25 can be controlled to undergo a phase transition.
[0054] The substrate layer 21 may include semiconductor materials such as silicon or germanium. The dielectric layer 22 may include insulating materials such as silicon oxide, silicon nitride or silicon oxynitride. The first electrode 23 and the second electrode 24 may include at least one of a variety of conductive materials such as copper, tungsten, titanium nitride, tantalum nitride, tungsten nitride, tungsten carbide and doped Si.
[0055] Figure 4 Schematic diagram of the structure of the memory chip 100 of some other embodiments provided by the present application. Figure 4 As shown, the memory chip 100 may adopt a sinker contact structure, and a portion of the phase change layer 25 is located in a small-sized sinker hole, thereby achieving the definition of the size of the memory cell 10 . Figure 4 The structure of the memory chip 100 is similar to Figure 3 The structure of the memory chip 100 shown is basically similar, and the similarities are not repeated. The differences include that the dielectric layer 22 includes a sink hole 221. The sink hole 221 is sunken from the surface of the dielectric layer 22 away from the substrate layer 21 to the surface of the dielectric layer 22 close to the substrate layer 21. The sink hole 221 exposes the columnar contact portion 231 of the first electrode 23. A portion of the phase change layer 25 is located in the sink hole 221. The area where the portion of the phase change layer 25 located in the sink hole 221 contacts the columnar contact portion 231 defines a phase change region.
[0056] From this we can see that Figures 2 to 4 The memory cell 10 of the memory chip 100 may adopt different structural designs. However, the memory cell 10 includes a phase change layer and two electrodes respectively located on both sides of the phase change layer.
[0057] Figures 2 to 4The phase change layers in the memory 300 all include phase change materials. The phase change material is a storage medium of the memory 300, which directly affects the performance of the memory 300. For example, the crystallization speed, crystallization temperature, amorphous phase stability, thermal stability, resistance window, cycle characteristics of the phase change material, and the adhesion between the phase change material and the electrode will affect the performance of the memory 300.
[0058] In some embodiments of the present application, the phase change material includes a base material, an Hf (hafnium) element, and an A element. The base material includes at least one element of Ge (germanium), Sb (antimony), and Te (tellurium). The A element includes at least one element of N, O, and Si.
[0059] The matrix material includes at least one element of Ge, Sb and Te, which can improve the crystallization speed of the phase change material and ensure that the memory 300 has a faster write (SET) speed.
[0060] The Hf element can inhibit the two-stage crystallization phenomenon of the base material during the crystallization process, further improve the crystallization speed of the phase change material, further improve the writing speed of the memory 300 including the phase change material, and thus improve the operation speed of the phase change memory. In addition, the Hf element can increase the crystallization temperature of the phase change material, improve the thermal stability of the phase change material in the amorphous state, and thus improve the high-temperature reliability of the memory 300, thereby improving the data retention of the device.
[0061] Element A can inhibit the phase separation phenomenon of the matrix material during the crystallization process, refine the grain size of the phase change material during the crystallization process, and improve the problem of forming large-sized grains during the crystallization process, thereby improving the cycle durability and resistance window of the memory 300 between the writing process and the erasing (Reset) process. In addition, element A and the constituent elements of the matrix material have strong bonding capabilities. The addition of element A can strengthen the bonding strength of the phase change material and improve the adhesion between the phase change material and the electrode, thereby improving the strength of the phase change material and reducing the risk of peeling between the phase change layer and the electrode. In addition, the addition of element A can also improve the consistency of small-size devices and achieve an increase in the yield of the memory 300.
[0062] It should be noted that the cycle durability is the maximum number of cycles for the phase change material to undergo a reversible phase change between the amorphous state (the phase change material is in a high resistance state) and the crystalline state (the phase change material is in a low resistance state), that is, the durability life. The greater the maximum number of cycles, the better the cycle durability. The storage window is the ratio of the resistance value of the phase change material in the amorphous state (Reset resistance) to the resistance value of the phase change material in the crystalline state (SET resistance). The larger the storage window, the larger the switching ratio of the memory 300.
[0063] Therefore, co-doping the matrix material with Hf element and A element can simultaneously improve the operating speed and durability of the memory 300 , enhance the performance reliability and data retention of the memory 300 , and facilitate the large-scale production of the memory 300 including the phase change material.
[0064] In some embodiments, in the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%. In this way, the write speed of the memory 300 including the phase change material is further improved, thereby improving the operating speed of the phase change memory. In addition, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%, which is beneficial to improving the resistance window of the memory.
[0065] Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 1% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 2% and less than or equal to 17%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 3% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 4% and less than or equal to 12%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 5% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 7% and less than or equal to 9%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 0.01% and less than or equal to 8%. Optionally, in the phase change material, the atomic percentage of the Hf element may be greater than or equal to 0.1% and less than or equal to 6%. Optionally, in the phase change material, the atomic percentage of the Hf element may be greater than or equal to 10% and less than or equal to 18%, so as to significantly increase the crystallization temperature of the phase change material.
[0066] For example, in the phase change material, the atomic percentage of the Hf element can be 0.02%, 0.05%, 0.08%, 0.2%, 0.5%, 0.8%, 1.2%, 1.5%, 1.8%, 2.2%, 2.5%, 2.8%, 3.2%, 3.5%, 3.8%, 4.2%, 4.5%, 4.8%, 5.2%, 5.5%, 5.8%, 6.2%, 6.5%, 6.8%, 7.2%, 7.5%, 7.8%, 8.2%, 8.5%, 8.8 %, 9.2%, 9.5%, 9.8%, 10.2%, 10.5%, 10.8%, 11.2%, 11.5%, 11.8%, 12.2%, 12.5%, 12.8%, 13.2%, 13.5%, 13.8%, 14.2%, 14.5%, 14.8%, 15.2%, 15.5%, 15.8%, 16.2%, 16.5%, 16.8%, 17.2%, 17.5%, 17.8%, 18.2%, 18.8 or 19.2%.
[0067] In some embodiments, in the phase change material, the percentage of the number of atoms of the A element is greater than 0% and less than or equal to 20%. In this way, the performance reliability and data retention of the memory 300 are improved. In addition, the percentage of the number of atoms of the A element is greater than 0% and less than or equal to 20%, which is beneficial to improving the overall performance of the memory.
[0068] Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 2% and less than or equal to 17%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 3% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 4% and less than or equal to 12%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 5% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 7% and less than or equal to 9%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 0.01% and less than or equal to 8%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 0.5% and less than or equal to 5.5%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 10% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 12% and less than or equal to 17%.
[0069] For example, in the phase change material, the atomic percentage of element A can be 0.02%, 0.05%, 0.08%, 0.2%, 0.5%, 0.8%, 1.2%, 1.5%, 1.8%, 2.2%, 2.5%, 2.8%, 3.2%, 3.5%, 3.8%, 4.2%, 4.5%, 4.8%, 5.2%, 5.5%, 5.8%, 6.2%, 6.5%, 6.8%, 7.2%, 7.5%, 7.8%, 8.2%, 8.5%, 8.8%, 9.2%, 9.5%, 9.8%, 10.2%, 10.5%, 10.8%, 11.2%, 11.5%, 11.8%, 12.2%, 12.5%, 12.8%, 13.2%, 13.5%, 13.8%, 14.2%, 14.5%, 14.8%, 15.2%, 15.5%, 15.8%, 16.2%, 16.5%, 16.8%, 17.2%, 17.5%, 17.8%, 18%, 18.2%, 18.5%, 18.8%, 19.2%, 19.5% or 19.8%.
[0070] In some embodiments, in the phase change material, the absolute value of the difference between the atomic number percentage of the Hf element and the atomic number percentage of the A element is less than or equal to 1%. In this way, the atomic number percentages of the Hf element and the A element are close, and the proportions of the two are coordinated to simultaneously improve the operating speed and durability of the memory 300, improve the performance reliability and data retention of the memory 300, and facilitate the large-scale production of the memory 300 including the phase change material.
[0071] In some embodiments, the A element includes at least one of N and O. Optionally, the A element includes O. Optionally, the A element includes N. Optionally, the A element includes N and O. In this way, since the N and O elements are easy to dope and control in the semiconductor process, the N and O elements have better process compatibility and less side effects on semiconductor processes such as etching, which is conducive to promoting the application of phase change materials in phase change storage.
[0072] In some embodiments, when the A element includes the N element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 0.01% and less than or equal to 10%, and the atomic number percentage of the N element is greater than or equal to 0.01% and less than or equal to 10%. In this way, not only can the second-stage crystallization of the phase change material be significantly inhibited to increase the crystallization speed and stability after crystallization, but the phase change material can also have a higher Reset resistance, thereby improving the resistance window. Optionally, when the A element includes the N element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 1% and less than or equal to 6%, and the atomic number percentage of the N element is greater than or equal to 1% and less than or equal to 6%.
[0073] In some embodiments, when the A element includes the N element, in the phase change material, the absolute value of the difference between the atomic number percentage of the Hf element and the atomic number percentage of the N element is less than or equal to 2%. In this way, the second stage crystallization of the phase change material can be more obviously suppressed to improve the crystallization speed and stability after crystallization, and the phase change material can also have a higher reset resistance, thereby improving the resistance window. Optionally, the difference between the atomic number percentage of the Hf element and the atomic number percentage of the N element is less than or equal to 2%, 1.5% or 1%.
[0074] In some embodiments, when the A element includes the O element, in the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%, and the atomic number percentage of the O element is greater than or equal to 0.1% and less than or equal to 20%. In this way, not only can the crystallization temperature be significantly increased, but also the phase change material can have a higher Reset resistance, thereby increasing the resistance window. Optionally, when the A element includes the O element, in the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 10%, and the atomic number percentage of the O element is greater than or equal to 0.5% and less than or equal to 10%.
[0075] In some embodiments, when the A element includes the O element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 10% and less than or equal to 20%, and the atomic number percentage of the O element is greater than or equal to 0.5% and less than or equal to 3%. In this way, not only can the crystallization temperature be significantly increased, but also the phase change material can have a higher Reset resistance, thereby increasing the resistance window. Optionally, when the A element includes the O element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 12% and less than or equal to 18%, and the atomic number percentage of the O element is greater than or equal to 0.5% and less than or equal to 2.5%.
[0076] In some embodiments, when the A element includes the O element and the N element, in the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%, the atomic number percentage of the O element is greater than or equal to 0.5% and less than or equal to 3%, and the atomic number percentage of the N element is greater than or equal to 0.01% and less than or equal to 10%. In this way, not only can the second-stage crystallization of the phase change material be significantly suppressed to increase the crystallization speed and stability after crystallization, but also the crystallization temperature can be significantly increased, and the phase change material can also have a higher reset resistance, thereby increasing the resistance window.
[0077] In some embodiments, the matrix material includes Ge, Sb and Te. In the phase change material, the atomic percentage of Ge is greater than or equal to 0% and less than or equal to 50%, the atomic percentage of Sb is greater than or equal to 10% and less than or equal to 50%, and the atomic percentage of Te is greater than or equal to 40% and less than or equal to 70%. In this way, the crystallization speed of the phase change material can be further improved, ensuring that the memory 300 has a faster write (SET) speed.
[0078] Optionally, in the phase change material, the percentage of the number of atoms of Ge element is greater than or equal to 2% and less than or equal to 45%. Optionally, in the phase change material, the percentage of the number of atoms of Ge element is greater than or equal to 5% and less than or equal to 40%. Optionally, in the phase change material, the percentage of the number of atoms of Ge element is greater than or equal to 8% and less than or equal to 35%. Optionally, in the phase change material, the percentage of the number of atoms of Ge element is greater than or equal to 9% and less than or equal to 25%. Optionally, in the phase change material, the percentage of the number of atoms of Ge element is greater than or equal to 10% and less than or equal to 15%.
[0079] Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 12% and less than or equal to 48%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 15% and less than or equal to 45%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 20% and less than or equal to 42%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 25% and less than or equal to 40%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 35% and less than or equal to 45%.
[0080] Optionally, in the phase change material, the atomic number percentage of the Te element is greater than or equal to 40% and less than or equal to 65%. Optionally, in the phase change material, the atomic number percentage of the Te element is greater than or equal to 42% and less than or equal to 60%. Optionally, in the phase change material, the atomic number percentage of the Te element is greater than or equal to 44% and less than or equal to 55%.
[0081] In some embodiments, when the A element is the N element, the chemical formula of the phase change material is (N) x1 (Hf) y1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1 . Wherein, x1 represents the atomic percentage of N element, y1 represents the atomic percentage of Hf element, m1 / n1 / k1 represents the atomic percentage of Ge, Sb and Te, and m1+n1+k1=100%. 0<x1≤10%, 0<y1≤10%, 0≤m1≤50%, 0≤n1≤50%, 40%≤k1≤70%. In this way, the resistance window of the phase change material is improved, the adhesion between the phase change material and the electrode is increased, and the cycle durability of the device is improved.
[0082] Optionally, when the A element is the N element, 0.1%≤x1≤8%, 0.1%≤y1≤8%, 8%≤m1≤15%, 32%≤n1≤45%, 40%≤k1≤60%. In this way, the resistance window of the phase change material can be further improved, the adhesion between the phase change material and the electrode can be increased, and the cycle durability of the device can be improved.
[0083] Optionally, when the A element is the N element, 1%≤x1≤8%, 1%≤y1≤8%, 10%≤m1≤13%, 37%≤n1≤44.5%, 43%≤k1≤50%. In this way, the resistance window of the phase change material can be further improved, the adhesion between the phase change material and the electrode can be increased, and the cycle durability of the device can be improved.
[0084] Optionally, when the A element is the N element, 2%≤x1≤5%, 2%≤y1≤6%, 10%≤m1≤13%, 37%≤n1≤44.5%, 43%≤k1≤50%. In this way, the resistance window of the phase change material can be further improved, the adhesion between the phase change material and the electrode can be increased, and the cycle durability of the device can be improved.
[0085] In some embodiments, the chemical formula of the phase change material includes (Ge 10 Sb 40 Te 50 ) 91 Hf5N4、(Ge12.5 Sb 37.5 Te 50 ) 91 Hf5N4、(Ge1 2.5 Sb 37.5 Te 50 ) 88 Hf8N4 or (Ge 11.12 Sb 44.44 Te 44.44 ) 91 At least one of Hf5N4.
[0086] Among them, the phase change material includes (Ge 10 Sb 40 Te 50 ) 91 Hf5N4 can better ensure that the crystallization temperature of the phase change material is higher than 200°C, thereby improving the thermal stability of the phase change material.
[0087] Among them, the phase change material includes (Ge 12.5 Sb 37.5 Te 50 ) 91 Hf5N4 and (Ge1 2.5 Sb 37.5 Te 50 ) 88 Hf8N4 can better improve the adhesion between the phase change material and the tungsten electrode.
[0088] Among them, the phase change material includes (Ge 11.12 Sb 44.44 Te 44.44 ) 91 Hf5N4 can better improve the cycle times and cycle stability of the device.
[0089] In some embodiments, when the A element is the O element, the chemical formula of the phase change material is (O) x2 (Hf) y2 (Ge m2 Sb n2 Te k2 ) 1-x2-y2 . Wherein, x2 represents the atomic percentage of O element, y2 represents the atomic percentage of Hf element, m2 / n2 / k2 represents the atomic percentage of Ge, Sb and Te, and m2+n2+k2=100%. 0.1%≤x2≤3%, 10%≤y2≤20%, 0≤m2≤50%, 0≤n2≤50%, 40%≤k2≤70%. In this way, the resistance window of the phase change material can be improved, the adhesion between the phase change material and the electrode can be increased, and the cycle durability of the device can be improved.
[0090] In some embodiments, the crystallization temperature of the phase change material is greater than or equal to 150° C. and less than or equal to 300° C. In this way, the stability of the phase change material in the amorphous state is improved while the writing speed is improved. If the crystallization temperature is too low, it is not conducive to improving the stability of the phase change material in the amorphous state. If the crystallization temperature is too high, it is not conducive to improving the writing speed.
[0091] Optionally, the crystallization temperature of the phase change material is greater than or equal to 180° C. and less than or equal to 280° C. Optionally, the crystallization temperature of the phase change material is greater than or equal to 200° C. and less than or equal to 260° C. Optionally, the crystallization temperature of the phase change material is greater than or equal to 210° C. and less than or equal to 250° C.
[0092] In some embodiments, the resistance window of the phase change material is greater than or equal to 1 and less than or equal to 20000. In this way, the on / off ratio of the memory 300 is improved.
[0093] Optionally, the resistance window of the phase change material is greater than or equal to 20 and less than or equal to 10000. Optionally, the resistance window of the phase change material is greater than or equal to 30 and less than or equal to 5000. Optionally, the resistance window of the phase change material is greater than or equal to 30 and less than or equal to 1000. Optionally, the resistance window of the phase change material is greater than or equal to 40 and less than or equal to 200. Optionally, the resistance window of the phase change material is greater than or equal to 50 and less than or equal to 150. Optionally, the resistance window of the phase change material is greater than or equal to 70 and less than or equal to 120.
[0094] In some embodiments, the resistance of the phase change material in the amorphous state may be greater than or equal to 1 MΩ and less than or equal to 2 MΩ. Alternatively, the resistance of the phase change material in the amorphous state may be greater than or equal to 1.1 MΩ and less than or equal to 1.8 MΩ. This is beneficial to improving the storage window of the phase change material.
[0095] In some embodiments, the resistance of the phase change material in the crystalline state may be greater than or equal to 13 kΩ and less than or equal to 16 kΩ. Alternatively, the resistance of the phase change material in the crystalline state may be greater than or equal to 13.5 kΩ and less than or equal to 15.5 kΩ. This is beneficial to improving the storage window of the phase change material.
[0096] In some embodiments, the write speed of the memory is greater than or equal to 50 ns / time. Thus, the write speed of the memory can be as low as 50 ns / time, and the memory has a faster write speed.
[0097] It should be noted that in an actual write operation of a storage array, a complete write operation process includes an addressing phase, a pre-operation phase, and an actual write operation phase. The write speed of the present application is the speed of the actual write operation phase.
[0098] In some embodiments, the memory has a cycle capacity greater than or equal to 10 8 times. In this way, the cycle endurance of the memory is improved.
[0099] In some embodiments, the adhesion between the electrode and the phase change layer is characterized by an energy release rate, and the energy release rate is greater than or equal to 0.8 J / m 2 In this way, the risk of peeling between the phase change layer and the electrode is reduced. Optionally, the energy release rate is greater than or equal to 0.85 J / m 2 Optionally, the energy release rate is greater than or equal to 0.9 J / m 2 .
[0100] In some embodiments, the electrode includes at least one of a metal material and a non-metal material. The metal material includes at least one of tungsten (W), tungsten nitride (WN), titanium (Ti), titanium nitride (TiN) and WSiN. The non-metal material includes at least one of carbon, nitrogen, oxygen and silicon. Optionally, the electrode includes tungsten. In this way, the electrode has better adhesion with the phase change material, further reducing the risk of peeling between the electrode and the phase change material.
[0101] It can be seen from this that the selection of constituent elements and the content of constituent elements of the phase change material of the present application can improve the operating speed and durability of the memory 300, and can also improve the performance reliability, data retention, process compatibility and process yield of the memory 300, which is conducive to the large-scale production of the memory 300 including the phase change material.
[0102] The present application also provides a method for preparing the above phase change material, the preparation method comprising the following steps:
[0103] Providing a first target, a second target, and a third target, wherein the first target includes at least one element of Ge, Sb, and Te, the second target includes Hf, and the third target includes A, wherein A includes at least one element of N, O, and Si; and
[0104] The phase change material is formed by using a first target, a second target and a third target.
[0105] In some embodiments, forming a phase change material using the first target material, the second target material, and the third target material includes: forming the phase change material using a deposition process or a growth process. The deposition process includes but is not limited to chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD), sputtering, metal organic chemical vapor deposition (MOCVD), or atomic layer deposition (ALD).
[0106] It is understandable that the phase change material may be formed using a single target material including at least one element among Ge, Sb and Te, Hf element and A element.
[0107] The performance of the above phase change material is verified in combination with the embodiments and comparative examples below.
[0108] Resistance-Temperature Curve Test
[0109] The test process of the resistance-temperature curve test includes a heating process and a cooling process. The heating process is to heat from room temperature to 400°C at a rate of 5°C / min in a nitrogen atmosphere; the cooling process is to cool from 400°C to room temperature naturally.
[0110] Example 1
[0111] Table 1 Composition and crystallization temperature of the phase change material of Example 1
[0112] Composition of phase change materials Crystallization temperature(℃) Example 1 <![CDATA[(Ge 10 Sb 40 Te 50 ) 91 Hf5N4]]> 218.25
[0113] From Table 1, it can be seen that the matrix material composed of Ge, Sb and Te doped with Hf and N elements at the same time can ensure that the crystallization temperature of the phase change material is higher than 200° C., thereby improving the thermal stability of the phase change material.
[0114] And, combined with Figure 5 From the heating curve d11, it can be seen that when Hf and N elements are simultaneously doped into the matrix material including Ge, Sb and Te, the two-stage crystallization phenomenon can be effectively suppressed, which is beneficial to improving the crystallization rate of the phase change material and the stability of the crystalline phase after the first-stage crystallization.
[0115] Adhesion test
[0116] The adhesion test method includes the following steps:
[0117] A first carbon layer (C1, with a thickness greater than or equal to 20 nanometers), a first tungsten electrode layer (W1, with a thickness greater than or equal to 3 nanometers), a phase change layer (PCM, with a thickness greater than or equal to 40 nanometers), a second tungsten electrode layer (W2, with a thickness greater than or equal to 3 nanometers) and a second carbon layer (C2, with a thickness greater than or equal to 20 nanometers) are sequentially formed on a first silicon substrate, and a second silicon substrate identical to the first silicon substrate is bonded to the second carbon layer (C2) by an epoxy resin adhesive to obtain a test sample;
[0118] The test sample is stretched frontally to apply tension to the first silicon substrate and the second silicon substrate until the first silicon substrate and the second silicon substrate are separated, and the energy release rate required for separation is recorded.
[0119] Comparative Example 1 and Examples 2 to 3
[0120] Table 2 Composition and energy release rate of phase change materials of comparative example 1 and examples 2 to 3
[0121] Composition of phase change materials Electrode Materials <![CDATA[Energy release rate (J / m 2 )]]> Comparative Example 1 <![CDATA[Ge 12.5 Sb 37.5 You 50 ]]> Tungsten 0.65 Example 2 <![CDATA[(Ge 12.5 Sb 37.5 Te 50 ) 91 Hf5N4]]> Tungsten 0.91 Example 3 <![CDATA[(Ge 12.5 Sb 37.5 The 50 ) 88 Hf8N4]]> Tungsten 0.8
[0122] Combined with Table 2, it can be seen that the energy release rate corresponding to Example 2 and Example 3 is greater than or equal to 0.8 J / m 2 , which is significantly greater than the energy release rate of 0.65 J / m corresponding to Comparative Example 1 2 .
[0123] Therefore, doping the matrix material including Ge, Sb and Te with Hf and N elements simultaneously can better enhance the adhesion between the phase change material and the tungsten electrode.
[0124] Tests of SET speed, cycle characteristics and resistance window
[0125] Example 4
[0126] Table 3 Composition of phase change material and results of resistance window test of Example 4
[0127]
[0128]
[0129] Combination Figure 6 It can be seen that for Example 4, Hf and N elements are doped simultaneously with the matrix material including Ge, Sb and Te, and the erasure times are 10 8 The resistance remains high even after 10 writes. 8 The resistance still remains low when the device is cycled for 10 times. 8Therefore, doping the matrix materials including Ge, Sb and Te with Hf and N elements simultaneously can increase the number of cycles and cycle stability of the device, thereby improving the cycle durability of the device.
[0130] Combination Figure 7 It can be seen that when the write speed is 50 ns / time, the resistance can be changed from high resistance to low resistance in the voltage range of 0.8 V to 1.7 V. It can be seen that the phase change material of Example 4 allows the write speed of the device to be as low as 50 ns / time. Therefore, the simultaneous doping of the Hf element and the N element into the matrix material including Ge, Sb and Te can improve the write speed of the device.
[0131] Combining Table 3 and Figure 8 It can be seen that when Hf and N are doped simultaneously in the matrix material including Ge, Sb and Te, the resistance value of the erase resistor is larger and the corresponding resistance window is also larger. Therefore, doping Hf and N elements simultaneously in the matrix material including Ge, Sb and Te can significantly increase the resistance window of the phase change material.
[0132] The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technical personnel in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A phase change material, characterized in that: The phase change material comprises: Base material; The Hf element; and The A element includes at least one element selected from the group consisting of N, O and Si.
2. The phase change material according to claim 1, characterized in that: In the phase change material, the atomic number percentage of the Hf element is greater than 0% and less than or equal to 20%.
3. The phase change material according to claim 2, characterized in that: In the phase change material, the atomic number percentage of the A element is greater than 0% and less than or equal to 20%.
4. The phase change material according to claim 3, characterized in that: In the phase change material, an absolute value of a difference between an atomic percentage of the Hf element and an atomic percentage of the A element is less than or equal to 1%.
5. The phase change material according to any one of claims 1 to 4, characterized in that: The matrix material includes at least one element of Ge, Sb and Te.
6. The phase change material according to claim 1, characterized in that: The matrix material includes Ge, Sb and Te elements; In the phase change material, the atomic number percentage of Ge element is greater than or equal to 0% and less than or equal to 50%, the atomic number percentage of Sb element is greater than or equal to 10% and less than or equal to 50%, and the atomic number percentage of Te element is greater than or equal to 40% and less than or equal to 70%.
7. The phase change material according to claim 6, characterized in that: The general chemical formula of the phase change material is (N) x1 (Hf) y1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1 ; Among them, x1 represents the atomic number percentage of N element, y1 represents the atomic number percentage of Hf element, m1 / n1 / k1 represents the atomic number percentage of Ge, Sb and Te, 0<x1≤10%, 0<y1≤10%, 0≤m1≤50%, 0≤n1≤50%, 40%≤k1≤70%.
8. The phase change material according to claim 1 or 7, characterized in that: The phase change material includes (Ge 10 Sb 40 Te 50 ) 91 Hf5N4、(Ge 12.5 Sb 37.5 Te 50 ) 91 Hf5N4、(Ge1 2.5 Sb 37.5 Te 50 ) 88 Hf8N4 and (Ge 11.12 Sb 44.44 Te 44.44 ) 91 At least one of Hf5N4.
9. The phase change material according to claim 1, characterized in that: The crystallization temperature of the phase change material is greater than or equal to 150° C. and less than or equal to 300° C.
10. A phase change memory, characterized in that: The phase change memory comprises the phase change material according to any one of claims 1-9.